2007
DOI: 10.1016/j.hrtlng.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Family presence and surveillance during weaning from prolonged mechanical ventilation

Abstract: Critical care clinicians influence families' acquisition of interpretive surveillance skills at the bedside of patients who are being weaned from LTMV. This study provides a potentially useful conceptual framework of family behaviors with long-term critically ill patients that could enhance the dialogue about family-centered care and guide future research on family presence in the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 38 publications
(33 reference statements)
4
54
0
2
Order By: Relevance
“…It was crucial for going ''backstage'' that they dared to trust the staff. This is in accordance with Burr, 1996Burr, , 1998Happ et al, 2007;Hupcey, 1999;Molter, 1979. One strategy used to create this interplay is the unit's adoption of a family-centred philosophy of care (Davidson et al, 2007;Mitchell and Chaboyer, 2010;Mitchell et al, 2009;Mitchell, 2008), including the following core concepts: dignity and respect, information sharing, participation and collaboration.…”
Section: Discussionsupporting
confidence: 90%
“…It was crucial for going ''backstage'' that they dared to trust the staff. This is in accordance with Burr, 1996Burr, , 1998Happ et al, 2007;Hupcey, 1999;Molter, 1979. One strategy used to create this interplay is the unit's adoption of a family-centred philosophy of care (Davidson et al, 2007;Mitchell and Chaboyer, 2010;Mitchell et al, 2009;Mitchell, 2008), including the following core concepts: dignity and respect, information sharing, participation and collaboration.…”
Section: Discussionsupporting
confidence: 90%
“…Most reviews of weaning from mechanical ventilation have examined only quantitative data [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Range of health care professionals [25][26][27][28][29][30][31][32][33][34][35] Patients only [36][37][38][39][40][41][42][43][44][45] Physicians only (intensivists or anesthetists working in intensive care units) [46][47][48][49] Patients' family members 50,51 Patients and nurses Participant interviews and observation 12,13,27,28,[31][32][33]40<...>…”
Section: Discussionmentioning
confidence: 99%
“…The articles on end-of-life care and on patients' families in the ICU are closely intertwined, with the exception of 1 study 40 in which the researchers focused on the presence of patients' families as the patients were weaned from mechanical ventilation. In this study, patients' family members were observed not just touching and talking to patients but also providing interpretive and protective surveillance for them.…”
Section: Families and End-of-life Carementioning
confidence: 99%